Mulinum spinosum root extract, rich in antioxidant compounds, mitigates harmful effects in mice with diet-induced metabolic syndrome - Silvia Berruezo; Susana Ferreyra; Ariel Fontana; Matilde de Paola; María Belén Pérez; Celina Scapini; Cecilia Cremer; Claudia Castro (Elsevier, 2022)
Background: Metabolic syndrome (MetS) is a health issue with a high incidence in adult population. Using herbal medicines for the management of serious complications of MetS, such as dyslipidemia and hyperglycemia, is highly promising. An aqueous extract from Mulinum spinosum (M. spinosum), traditionally used as hyperglycemic and anti-inflammatory, could have beneficial effects on the treatment of MetS.Purpose: The present study was aimed to characterize the composition of M. spinosum roots decoction, and to evaluate antidiabetic, antilipemic and antioxidant effects in an animal model of MetS.Study design and methods: M. spinosum roots extract was characterized using high-performance liquid chromatography coupled with diode array detection (HPLC-DAD) method. Total Phenolic Content (TPC) was spectrophotometrically measured and the antioxidant capacity was determined by the oxygen radical absorbance capacity (ORAC) assay. To generate the MetS model, adult male C57BL/6 mice were fed with a 20% w/v fructose (Fru) in drinking water combined with 30% w/w high fat diet (HFD) over a period of 12 weeks. M. spinosum aqueous extracts (3 or 6 g/kg/day) were administered in drinking water together with Fru-HFD. At the end of the exposure period, mice were weighed and glucose tolerance test was determined. After sacrifice, adipose tissues were isolated and blood samples were collected to evaluate lipid profile, lipid peroxidation level (LPO) and ferric reducing antioxidant power (FRAP).Results: The characterization of M. spinosum revealed the presence of caffeic acid, trans-resveratrol, kaempferol-3-glucoside, (-)-epicatechin, (-)-gallocatechin gallate, (-)-epigallocatechin and (+)-catechin. A high antioxidant capacity of the extract was revealed by ORAC test.  Mice fed a Fru-HF diet and treated with M. spinosum, reduced diet-induced weight gain and significantly decreased mesenteric fat compared with Fru-HFD group (p<0.01). Post prandial glycaemia significantly diminished when mice were treated with M. spinosum, and also total cholesterol, LDL-cholesterol and triglycerides (TG) were reduced. Regarding the antioxidant effect of the consumption of M. spinosum, we found a decrease in plasmatic LPO, and a significant increase in plasmatic FRAP.Conclusion: To our knowledge, the phenolic composition and the antioxidant capacity of M. spinosum roots decoction is reported for the first time. In addition, we provide evidence that M. spinosum root extract is a promising source of antioxidants able to alleviates Fru-HFD-induced metabolic alterations and slow the progression of MetS.